Organic Single‐Crystal Semiconductor Films on a Millimeter Domain Scale. (1st October 2015) - Kwon, Sooncheol; Kim, Jehan; Kim, Geunjin; Yu, Kilho; Jo, Yong‐Ryun; Kim, Bong‐Joong; Kim, Junghwan; Kang, Hongkyu; Park, Byoungwook; Lee, Kwanghee
Abstract : Nucleation and growth processes can be effectively controlled in organic semiconductor films through a new concept of template‐mediated molecular crystal seeds during the phase transition; the effective control of these processes ensures millimeter‐scale crystal domains, as well as the performance of the resulting organic films with intrinsic hole mobility of 18 cm 2 V –1 s –1 .